Health‐related quality of life in patients with chronic myeloid leukemia receiving first‐line therapy with nilotinib. Issue 10 (2nd March 2018) - Efficace, Fabio; Castagnetti, Fausto; Martino, Bruno; Breccia, Massimo; D'Adda, Mariella; Angelucci, Emanuele; Stagno, Fabio; Cottone, Francesco; Malato, Alessandra; Trabacchi, Elena; Capalbo, Silvana Franca; Gobbi, Marco; et al.
Abstract : BACKGROUND: Although a wealth of efficacy and safety data is available for many tyrosine kinase inhibitors used in chronic myeloid leukemia (CML), there is a dearth of information on their impact on patients' health‐related quality of life (HRQOL). The primary objective of this study was to evaluate HRQOL and fatigue outcomes in patients with CML receiving first‐line therapy with nilotinib. METHODS: This was a multicenter, prospective study enrolling 130 patients with chronic‐phase CML. HRQOL and fatigue were evaluated with the European Organization for Research and Treatment of Cancer Quality of Life Questionnaire‐Core 30 (EORTC QLQ‐C30) and its validated Fatigue module at the baseline and then at 3, 6, 12, 18, and 24 months. The primary prespecified HRQOL endpoints defined in the study protocol for longitudinal analysis were the Physical Functioning, Social Functioning, Role Functioning, and Fatigue scales. The remaining scales were investigated on an exploratory basis. RESULTS: The rate of baseline compliance with the HRQOL assessment was 95.4% (124 of 130), and the rate of overall compliance with HRQOL forms was 91%. Among the 4 prespecified primary HRQOL endpoints, statistically significant improvements over time were found for Physical Functioning ( P = .013), Role Functioning ( P = .004), and Fatigue ( P < .001). Clinically meaningful improvements were found already 3 months after the treatment start. The baseline patient self‐reported fatigue severity was an independent predictive factor for the achievement of a major molecular response with an odds ratio of 0.960 (95% confidence interval, 0.934‐0.988; P = .005). CONCLUSIONS: For most patients, HRQOL improvements with nilotinib occur during the early phase of therapy and are maintained over time. Also, a more systematic HRQOL evaluation during the diagnostic workup of CML may help to predict clinical outcomes. Cancer 2018;124:2228‐37 . © 2018 American Cancer Society . Abstract : Early health‐related quality of life improvements are observed with nilotinib therapy in patients with chronic myeloid leukemia. A baseline fatigue assessment may provide predictive information for the treatment response.